Digital assets in the context of the fourth industrial revolution, international integration, and Vietnamese law - Vien the Giang; Vo Thi My Huong (Cogent Social Sciences)
The legislative practice of many countries shows that, from a cautious attitude in recognizing this type of asset in law, many countries have issued legal provisions to solve arising problems including measures to handle situational, immediate, and detailed digital assets in the law to create an official and long-term legal basis to regulate legal relations related to digital assets. It can be affirmed that the formalization of digital assets in national law will create a legal basis for exploiting the values of digital assets, thereby encouraging the development of innovative enterprises, technological innovation; and this is also a basis for collecting taxes on profits earned from investment activities that contribute to shaping a trading market of a new asset. In the condition of having deeply integrated into the world economy and actively integrating into the world as well as adapting to the fourth industrial revolution, Vietnam needs to have a roadmap for implementation from the formalization of digital assets in the Civil Code to digital assets in business activities as well as digital asset transactions, in which priority is given to the recognition of digital assets as an asset in the Civil Code to “pave the way” for digital asset regulations in the business field and laws related to transactions, transfer, control and prevent crimes that may arise from transactions related to digital assets.